Comparison of long-term performances and final microbial compositions of anaerobic reactors treating landfill leachate - ÇALLI, BARIŞ; MERTOĞLU, BÜLENT (ELSEVIER SCI LTD, 2006)
Laboratory scale anaerobic upflow filter, sludge blanket and hybrid bed reactors were operated for 860 days in the treatment of high ammonia landfill leachate. Organic loading was gradually increased from 1.3 to 23.5 kg COD/m(3) day in the start-up period and then fluctuated according to the COD concentration of raw leachate. To prevent free ammonia inhibition, influent pH was reduced to 4.5 after Day 181 and consequently COD removal efficiencies above 80% were achieved in all reactors. However, the anaerobic filter and hybrid bed reactor were generally found slightly more efficient and stable than the UASB reactor. In addition to conventional anaerobic reactor control parameters, the complementary techniques of denaturing gradient gel electrophoresis (DGGE), cloning and fluorescent in situ hybridization (FISH) were used to identify and compare the microbial profiles in the reactors at Day 830. Molecular analyses revealed that acetoclastic Methanosaeta species were prevalent in all reactors and configuration did not have an impact on microbial diversity in the long-term. (c) 2005 Elsevier Ltd. All rights reserved.
Keywords: ammonia; anaerobic treatment; DGGE; FISH; landfill leachate; methanogens; MUNICIPAL SOLID-WASTE; QUANTIFICATION; DIVERSITY; SLUDGE